Challenges of diagnosis of COVID-19 in trauma patients: A case series. (July 2021) - Sabetian, Golnar; Feiz, Farnia; Shakibafard, Alireza; Fard, Hossein Abdolrahimzadeh; Sefidbakht, Sepideh; Jafari, Seyed Hamed; Abbasi, HamidReza; Zare, Masoomeh; Roudgari, Amir; Zand, Farid; Masjedi, Mansoor; Paydar, Shahram
Background: Diagnosis of COVID-19 can be challenging in trauma patients, especially those with chest trauma and lung contusion. Methods: We present a case series of patients from February and March 2020 who were admitted to our trauma center at Rajaee Hospital Trauma Center, in Shiraz, Iran and had positive SARS-CoV-2 PCR test or chest CT scan suggestive of COVID-19 and were admitted to the specific ICU for COVID-19. Results: Eight COVID-19 patients (6 male) with mean age of 40 (SD = 16.3) years old, were presented. All patients were cases of trauma injuries, with multiple injuries including chest trauma and lung contusion, admitted to our trauma center for management of their injuries, but they were diagnosed with COVID-19 as well. Two of them had coinfection of influenza type-B and SARS-CoV-2. All patients were treated for COVID-19 and three of them died; the rest were discharged from hospital. Conclusion: Since PCR for SARS-CoV-2 is not always sensitive enough to confirm the cause of pneumonia, chest CT manifestations can be helpful, though, they are not always differentiable from lung contusion. Therefore, both the CT scan and the clinical and paraclinical presentation and course of improvement can be beneficial in diagnosing COVID-19 in the trauma setting.